MANAGEMENT OF ACUTE SEVERE ULCERATIVE COLITIS: A CLINICAL UPDATE - SOBRADO,Carlos Walter (2016)
ABSTRACT Introduction: Acute severe colitis is a potentially lethal medical emergency and, even today, its treatment remains a challenge for clinicians and surgeons. Intravenous corticoid therapy, which was introduced into the therapeutic arsenal in the 1950s, continues to be the first-line treatment and, for patients who are refractory to this, the rescue therapy may consist of clinical measures or emergency colectomy. Objective: To evaluate the indications for and results from drug rescue therapy (cyclosporine, infliximab and tacrolimus), and to suggest a practical guide for clinical approaches. Methods: The literature was reviewed using the Medline/PubMed, Cochrane library and SciELO databases, and additional information from institutional websites of interest, by cross-correlating the following keywords: acute severe colitis, fulminating colitis and treatment. Results: Treatments for acute severe colitis have avoided colectomy in 60-70% of the cases, provided that they have been started early on, with multidisciplinary follow-up. Despite the adverse effects of intravenous cyclosporine, this drug has been indicated in cases of greater severity with an imminent risk of colectomy, because of its fast action, short half-life and absence of increased risk of surgical complications. Therapy using infliximab has been reserved for less severe cases and those in which immunosuppressants are being or have been used (AZA/6-MP). Indication of biological agents has recently been favored because of their ease of therapeutic use, their good short and medium-term results, the possibility of maintenance therapy and also their action as a "bridge" for immunosuppressant action (AZA/6-MP). Colectomy has been reserved for cases in which there is still no response five to seven days after rescue therapy and in cases of complications (toxic megacolon, profuse hemorrhage and perforation). Conclusion: Patients with a good response to rescue therapy who do not undergo emergency operations should be considered for maintenance therapy using azathioprine. A surgical procedure is indicated for selected cases.